The effect of power trainings on maximal power and anaerobic power in boxer - Ozdil, G.; Cakmakci, O. (Turkish Journal of Sport and Exercise, 2016)
The paper was done to analyze the effects of power trainings of different types as well as trainings performed for a 6-week competition period on maximal power and anaerobic power in the male boxers at an elite level. Within this study; 18 boxers aged between 19-25 who have actively engaged in the boxing branch, participated. Including the resistor group (LG) n:6, the dumbbell group (DG) n:6, the control group (CG) n:6, the three parts were included. The trial with resistance band and dumbbell mentioned was performed in the LG and DG groups between 9:00-10:00 a.m. for 5 days in a week during 6 weeks. Both trials were performed together doing boxing trainings aimed at competitions at 06:00 p.m. for 5 days in a week during 6 weeks. The control group did boxing trainings only aimed at competitions at 06:00 p.m. for 5 days in a week during 6 weeks. Their body weights, maximal power (bench press) and anaerobic power levels were measured with the Wingate test in all groups before a 6-week application, the same measurements were done after the application with resistance band and dumbbell as well as trainings in a 6-week competition period. When the findings were examined after the application with resistance band and dumbbell as well as a 6-week competition period trainings, there were not statistically significant differences in body weight (BW) levels between both in-group and between-group pre-tests and post-tests. When examining the anaerobic power and maximal bench parameters between the groups (LG, DG, CG), no significant differences were found in both pre-test comparisons and post-test comparisons. When looking at the pre-test and post-test variables in groups, there were statistically significant differences in the anaerobic power levels of the three groups (LG, DG, CG) (P<0.05). As the pre-test and post-test maximal bench levels were similar in the LG group, the maximal bench levels significantly increased in the DG and CG groups (P<0.05). As a result, it can be said that together with the period of competition with boxing training and resistance exercises do not provide a significant contribution for maximal strength and anaerobic force for boxers.